2012
DOI: 10.1021/nn302286w
|View full text |Cite
|
Sign up to set email alerts
|

The Subtle Chemistry of Colloidal, Quantum-Confined Semiconductor Nanostructures

Abstract: Nanoscale colloidal semiconductor structures with at least one dimension small enough to experience quantum confinement effects have captured the imagination and attention of scientists interested in controlling various chemical and photophysical processes. Aside from having desirable quantum confinement properties, colloidal nanocrystals are attractive because they are often synthesized in low-temperature, low-cost, and potentially scalable manners using simple benchtop reaction baths. Considerable progress i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 36 publications
0
45
0
Order By: Relevance
“…[23][24][25][26][27][28][29][30][31][32]119,120] As known to all, for semiconductor colloidal NCs to exhibit quantum confinement effect, the size must be comparable or smaller than the exciton Bohr radius. [23][24][25][26][27][28][29][30][31][32]119,120] As known to all, for semiconductor colloidal NCs to exhibit quantum confinement effect, the size must be comparable or smaller than the exciton Bohr radius.…”
Section: Tunable Photoluminescence Propertiesmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32]119,120] As known to all, for semiconductor colloidal NCs to exhibit quantum confinement effect, the size must be comparable or smaller than the exciton Bohr radius. [23][24][25][26][27][28][29][30][31][32]119,120] As known to all, for semiconductor colloidal NCs to exhibit quantum confinement effect, the size must be comparable or smaller than the exciton Bohr radius.…”
Section: Tunable Photoluminescence Propertiesmentioning
confidence: 99%
“…for quantum dots [9] or medical applications [8]). However, the controlled processing and assembly of very small nanoparticles into nanostructured materials are very challenging [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies focused on GeI 2 as a Ge(II) precursor and surprisingly, only a few studies which concentrated on the use of novel Ge precursors have been reported in the literature despite the success encountered for other semiconductors. 10,11 To the best of our knowledge, only Boyle et al have explored the reactivity of two families of tailored germanium(II) compounds: Ge(NR 2 ) 2 and Ge(OR) 2 , R being alkyl, aryl and silyl moities. 4,9,12 Unfortunately, the shape control remains unsatisfactory compared to other strategies presumably.…”
Section: Introductionmentioning
confidence: 99%